Entre la experiencia del vacío y el silencio - Mele, Jorge S (2008)
arquitectura
Keywords: CRITICA; ARGENTINA; BUENOS AIRES; VENTURA, DANIEL; VIVIENDAS MULTIFAMILIARES; VIVIENDAS URBANAS; TIPOLOGIAS; TRÍPLEX; CONSTRUCCION; HORMIGON